Factors Associated with Motivation to Provide Exclusive Breastfeeding among Post-ERACS Cesarean Section Mothers at RSIA Bina Medika, Indonesia - Wirasanti, Saksi; Vivi Silawati; Rukmaini (International Journal of Midwifery and Health Sciences, 2026)
Background: Exclusive breastfeeding is recommended for the first six months of life; however, its implementation remains suboptimal among post-cesarean mothers, particularly those undergoing the Enhanced Recovery After Caesarean Section (ERACS) protocol.Objective: This study aimed to analyze factors associated with maternal motivation to provide exclusive breastfeeding among post-ERACS mothers.Methods: A quantitative cross-sectional study was conducted among 60 postpartum mothers using total sampling. Data were collected using structured questionnaires and analyzed using Chi-Square tests.Results: Occupation, knowledge, attitude, self-efficacy, lifestyle, perceived benefits and barriers, sociocultural factors, and family support were significantly associated with maternal motivation (p < 0.05).Conclusion: Maternal motivation to provide exclusive breastfeeding is influenced by psychosocial, behavioral, and environmental factors.